Analytical music therapy - Eschen, Johannes Th (Jessica Kingsley Publishers, 2002)
This book brings together the professional experiences of eminent analytical music therapists from Europe and the USA. The book examines the origins and theory of AMT (including a contribution on the subject from Mary Priestley), before exploring its uses in various contexts. Chapters cover AMT in counselling and rehabilitation, with adults and children and with nonverbal clients. A concluding section discusses aspects of the training of music therapy students. Written by experienced and highly regarded analytic music therapists, and edited by Johannes Th. Eschen, one of the first ever AMT stu.